The giants of sales : what Dale Carnegie, John Patterson, Elmer Wheeler, and Joe Girard can teach you about real sales success - Sant, Tom (AMACOM, American Management Association, 2006)
Sales theories come and sales theories go, but nothing beats learning from the original masters. The Giants of Sales introduces readers to the techniques developed by four legendary sales giants, and offers concrete examples of how they still work in the 21st century.